Evaluation of the minimum age for consent to mental health treatment with the minimum age of criminal responsibility in children and adolescents: a global comparison - Noroozi, M; Singh, I; Fazel, M (BMJ Publishing Group, 2018)
Background In many countries, a young person who seeks medical care is not authorised to consent to their own assessment and treatment, yet the same child can be tried for a criminal offence. The absence of child and adolescent mental health legislation in most countries exacerbates the issues young people face in independently accessing mental healthcare. Countries with existing legislation rarely define a minimum age for mental health consent (MAMHC). In stark contrast, nearly all 196 nations studied maintain legislation defining a minimum age of criminal responsibility (MACR). Objective This review highlights inconsistent developmental and legal perspectives in defined markers of competency across medical and judicial systems. Methods A review of the MAMHC was performed and compared with MACR for the 52 countries for which policy data could be identified through publicly available sources. Findings Only 18% of countries maintain identifiable mental health policies specific to children’s mental health needs. Of those reviewed, only 11 nations maintained a defined MAMHC, with 7 of 11 having a MAMHC 2 years higher than the country’s legislated MACR. Conclusions With increasing scientific understanding of the influences on child and adolescent decision making, some investment in the evidence-base and reconciliation of the very different approaches to child and adolescent consent is needed. Clinical implications A more coherent approach to child and adolescent consent across disciplines could help improve the accessibility of services for young people and facilitate mental health professionals and services as well as criminal justice systems deliver optimal care.